Preliminary study demonstrating decreased eye blink rates in horses in response to induced stressors - Sylvia, E.; Stogryn, M.; Schittenhelm, J.; Bartkowski, S.; Merkies, K. (DCA Report; Nr. 044, 2014)
Horses demonstrate a variety of responses when introduced to stressful situations, e.g. ears pinned back, restless, head high. In other species such as humans or cattle, eye blink rate (EBR) is used as an indicator of stress. Increased EBR is associated with anxiety, lack of concentration and decreased performance in humans. Little research has been done on EBR in horses in response to stress, but it is hypothesized EBR in horses will differ when exposed to stressful situations. Six horses were randomly assigned to each of four treatments: 1) Control - horse in its normal paddock environment; 2) Separation - horse was removed from its paddock mates; 3) Feed restriction - feed was withheld for 5 min at regular feeding time; and 4) Fear test - an umbrella was suddenly opened and closed while horse was alone in the arena. Eye blink rates (blinks/min) were retrospectively determined by two independent observers from video recordings of each horse`s right eye for a duration of 1 minute. A one-way ANOVA with repeated measures was used to determine the effect of treatment on EBR, and Tukey`s Honest Significant Difference test was used to evaluate differences among treatments. Eye blink rates were highest in the Control treatment (38 blinks/mina), and decreased when varying stressors were introduced to the horses: 20 blinks/minb during separation; 18 blinks/minb during feed restriction; 10 blinks/minc during the fear test; a, b, c, differ P<0.0001. As prey animals, when horses perceive danger, they will raise their head to scan their surroundings and prepare for flight if the situation warrants it. The reduction in EBR in response to stressors may be caused by an increase in concentration, as has also been documented with humans. Eye blink rates are also positively correlated with dopamine levels, and thus may hold promise for a non-invasive relative measure of this hormone. While this study is limited due to the low number of subjects and lack of physiological measures, it provides a basis for further research. LP: Accurate assessment of behavioural responses as a communication tool between horses and humans is a constant challenge. If horses rely on their physical attributes to communicate, then humans can use physical indicators such as eye blink rate to detect changes in the emotional state of the horse. Eye blink rate as a measure of stress in horses has not been studied to date, but preliminary analysis indicates that eye blink rates appear to decrease when the horse is subjected to a stressful environment and this non-invasive measure may potentially be linked to circulating hormones.